POPULATION PROJECTION AND FACTOR ANALYSIS AFFECTING POPULATION GROWTH IN THE CITY MEDAN USING NON LINEAR TRENDS POLYNOMIC METHOD - Pertiwi, Fina Nur; Lubis, Riri Syafitri; Widyasari, Rina (Journal of Mathematics and Scientific Computing With Applications, 2021)
Non-linear trend is a measure of trend that has a model with quadratic equations, cubic and so on. The purpose of this research is to determine the population projection in Medan using a non-linear trend of the polynomial method (parabolic trend / quadratic trend) and to determine the factors that influence population growth in the city of Medan. From the results of data processing using the non-linear trend of the polynomial method, it is obtained that the projected number of population in 2029 will be 2645501 people, with The total male population is 1314713 and the female population is 1330788. When compared with the population in previous years, it can be seen that until 2029 the population in Medan will increase. Based on the research results from the factor analysis, it is known that the factors that are formed from the factor analysis process can be concluded that all the factors formed affect the population growth rate of Medan. The factors formed are birth (fertility), death (mortality) and migration.